Averaged Synthesis of the Optimal Control for a Wave Equation - Kapustyan, O. V.; Sukretna, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
For a wave equation, we determine an optimal control in the feedback form and prove the convergence of the constructed approximate control to the exact one.